(untitled) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2022)
Catfish is one of the fish that has a high economic value so that it becomes one of the export commodities to meet the consumption and protein needs of the community so that it is widely cultivated. In cultivation, catfish can be attacked by various diseases, one of which can be caused by bacteria. The bacteria that often cause death in fish, both marine and freshwater fish, is Yersinia spp. Yersinia spp is a group of gram-negative bacteria, in the form of bacilli and motile and is also reported to be one of the pathogenic diseases that often attack fish. samples were taken on August 12, 2021 from the mouth organs of catfish at the Hasanuddin University Education Animal Clinic. Samples were cultured in Tryptic Soy Agar (TSA) for 24 hours and then purified in Mac Conkey Agar (MCA). The culture results showed the presence of bacterial growth. Follow-up examination using a microscope and showed the presence of red (Gram negative) and bacilli-shaped bacteria.